The Effect of Using Zoom Application in English Learning for IPS Tenth Grade in SMA Negeri 3 Pematangsiantar - Anita Purba; Sinar Girsang (Program Studi Pendidikan Bahasa Inggris FKIP, 2022)
This study was aimed at investigating whether The object of the study is to know the effect of zoom application in English learning, at IPS tenth grade students of SMA Negeri 3 Pematangsiantar. This research was a qualitative approach. For the data collection the interview. The population of this study was the students the Tenth Grade in SMA Negeri 3 Pematangsiantar has take 12 students, and each class reseacher took 4 students. Based on the results of the study, the researcher concluded that many effects were found when learning to use the zoom application on both students and teachers.there are : Signal drop out, The teacher's voice is not clear, Network is not stable, Students are increasingly difficult to understand learning,Teachers who complain because students are hard to catch